AUDIT REPORT LAG OF LISTED COMPANIES IN INDONESIA STOCK EXCHANGE - Nur Mazkiyani; Sigit Handoyo (Jurnal Aplikasi Bisnis, 2017)
ABSTRACTRecently, the timeliness of audited financial statement contributed enormously in the consideration of decision-making process. Therefore, the audited financial statement must be published on time, as well as the availability and accuracy of the financial information required for shareholders, investors and other users as decision makers. Interval time to the completion of financial statement audit report can be measured by duration of the days required to obtain independent auditor report. The duration counted from the date of companies' financial statement year-end until the date of audit report, known as audit report lag. Previous research regarding audit report lag has been conducted, along with the results that show some of factors which are significantly affect audit report lag including; company size, profitability, public accounting firm, auditors’ opinion, leverage, solvability, type of industry and profit / loss operation. This research aims to analyze factors that affect audit report lag in some of public companies in Indonesia. This research examines the influence of company size, profitability, solvability, age of company, accounting firm size and audit committee towards audit report lag. The total sample consists of 332 firm-years observations of manufacturing companies listed in Indonesia Stock Exchange during 2009-2012. Analysis hypothesis is using multiple regressions. The results of multiple regression show that profitability and accounting firm size significantly influence audit report lag. Whereas, company size, solvability, age of company and audit committee does not influence audit report lag. Keywords: Audit report lag, company size, profitability, solvability, age of company, accounting firm size, audit committee. ABSTRAKAkhir-akhir ini, ketepatan waktu laporan keuangan yang telah diaudit memberikan kontribusi besar dalam pertimbangan proses pengambilan keputusan. Oleh karena itu, laporan keuangan yang telah diaudit harus dipublikasikan secara tepat waktu, karena ketersediaan dan juga keakuratan informasi keuangan diperlukan bagi pemegang saham, investor dan pengguna lain sebagai pengambil keputusan. Jangka waktu penyelesaian audit laporan keuangan dapat diukur berdasarkan lamanya hari yang dibutuhkan untuk memperoleh laporan auditor independen, terhitung sejak tanggal tahun tutup buku perusahaan sampai tanggal yang tertera pada laporan auditor independen, dikenal dengan audit report lag. Penelitian sebelumnya mengenai audit report lag telah dilakukan, dengan hasil yang menunjukkan beberapa faktor-faktor secara signifikan mempengaruhi audit report lag diantaranya; ukuran perusahaan, profitabilitas, ukuran kantor akuntan publik, auditor opinion, leverage, sovabiltas, jenis industri dan operasi laba/rugi. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi audit report lag di beberapa perusahaan di Indonesia. Penelitian ini menguji pengaruh ukuran perusahaan, profitabilitas, solvabilitas, umur perusahaan, ukuran kantor akuntan publik (KAP) dan komite audit terhadap audit report lag. Jumlah sampel penelitian terdiri dari 332 perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia untuk periode 2009-2012. Analisis hipotesis penelitian menggunakan regresi linear berganda. Hasil dari analisis regresi berganda menunjukkan profitabilitas dan ukuran kantor akuntan publik secara signifikan mempengaruhi audit report lag. Sedangkan ukuran perusahaan, solvabiltas, umur perusahaan dan komite audit tidak memiliki pengaruh terhadap audit report lag. Kata kunci: Audit report lag, ukuran perusahaan, profitabilitas, solvabilitas, umur perusahaan, ukuran kantor akuntan publik (KAP), komite audit.